Actors Determination Strategy in Registered Social Network Patents in the Framework of Rewards towards Inventors A Case Study: LIPI Registered Patents 2016 - Aris Yaman (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2016)
Patent is one of the lever factors in improving the nation's competitiveness. A reward to an inventor is one way that can be taken to increase the productivity and patent development in Indonesia. The social network analysis on the relationship of co-invention and registered patents can identify inventing actors who deserves the award. Joko Waluyo obtained an actor who is considered central to the co-invention social network relationships of registered patents in LIPI. It is based on the high value of betweeness and closeness to the node Joko Waluyo. In addition, it was found that the prolific inventor does not always mean a central actor in the social network.